Genome-wide snp microarray analysis among Malay sub-ethnic groups in peninsular Malaysia - Ab Rajab, Nur Shafawati (2013)

(untitled)
The use of advanced technology in the field of genetic had influenced and upgraded the dicipline and had leds to a lot of advances in the genetics of human populations. Among them, microarray of single nucleotide polymorphism (SNP) allows large coverage of the human genome. SNP microarray was used for this study to find and characterize genetic differences among Malays sub-ethnic groups in Peninsular Malaysia. The Malay sub-ethnic groups of Peninsular Malaysia consist of several sub-groups that differ in a variety of factors including language, history of migration to Malaysia, origins, customs and daily social life. One hundred and thirty five Malays participated in this study and consisted of Kelantan Malay, Minang Malay, Javanese Malay, Bugis Malay, Kedah Malay Champa Malay, Pattani Malay and Banjar Malay.